Veruntreute Geschichte - Dubrovic, Milan 1903-1994 (Zsolnay, 1985)
Milan Dubrovic: "Veruntreute Geschichte. Die Wiener Salons und Literatencafés". Paul Zsolnay Verlag, Wien-Hamburg 1985. 316 S., mit Abb., geb., 34,80 DM